Processed line aerogravity data over the Pine Island Glacier basin (2004/05 season) - Jordan, Tom; Ferraccioli, Fausto (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
During the austral summer of 2004/05 a collaborative US/UK field campaign undertook a systematic geophysical survey of the entire Amundsen Sea embayment using comparable airborne survey systems mounted in Twin Otter aircraft. Here we present the portion of the survey covering the Pine Island Glacier basin led by British Antarctic Survey. Operating from a temporary field camp (PNE, S 77deg34' W 095deg56'; we collected ~35,000 km of airborne survey data. Our aircraft was equipped with dual-frequency carrier-phase GPS for navigation, radar altimeter for surface mapping, wing-tip magnetometers, gravity meter, and a new ice-sounding radar system (PASIN). We present here the processed line aerogravity data collected using a LaCoste & Romberg air-sea gravity meter S83 mounted in the BAS aerogeophysically equiped Twin Otter aircraft. Data are provided as XYZ ASCII line data. : Airborne gravity are presented in Jordan et al. (2010) and Smith et al. (2013) along with details of data collection and processing steps. The dataset available here includes all channels from raw through to filtered and upward continued free air anomalies. Gravity processing steps were as follows: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 40 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = ((ST_real+CC)*0.9966)+(Beam_velocity*k_fac), k_fac=60/2.04, meter scale value =0.9966. Still readings are in mGal (Still), and were calculated assuming a linear best fit to the drift of the airborne meter observed at the start and end of every flight. Tie absolute gravity values for the survey (Base) were derived from land gravity measurements adjacent to the survey aircraft tied back to the gravity base station at Rothera Research Station. Airborne absolute gravity values (Abs_grav) = Rec_grav- Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984) Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Filtered free air anomaly (FAA_filt) used 9 km 1/2 wavelength space domain kernel filter (Holt et al., 2006). Final free air data (FAA_clip) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Upward continued free air anomaly (FAA_2400m) was produced by upward continuing each line segment from the collected flight altitude to 2400 m, the highest altitude in the survey. Note no levelling has been applied to the free air gravity data. Description of channels: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1:12 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction (mGal) EotvosCor Eotvos correction (mGal) LatCor Latitude correction (mGal) FaCor Free air correction (mGal) HaccCor Horizontal acceleration correction (mGal) Free air Channels Free_air Un-filtered free air anomaly (mGal) FAA_filt Filtered free air anomaly (mGal) FAA_clip Filtered free air anomaly masked (mGal) FAA_Level Levelled, filtered free air anomaly data (mGal) FAA_2400m Upward continued free air anomaly to an altitude of 2400 m (mGal) *Projected coordinates (x and y) are in Polar Stereographic defined as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin 0.994 False easting 0 False northing 2082760.109